Non-random mating activity of colour morphs of ladybird Harmonia axyridis (Coleoptera: Coccinellidae) - Awad, Mona Abdel Rahman; Kalushkov, Plamen; Karabüyük, Feray; Nedvěd, Oldřich (Česká společnost zoologická, 2015)
Ladybird beetles are highly sexually active as they mate often and for a long time. In some of the species that are polymorphic in terms of their elytral colouration there is a high proportion of melanic males in mating pairs. We recorded the number of individuals of Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae) of both sexes and of all colour morphs (light succinea, melanic spectabilis and conspicua), and the numbers of the different morphs mating in May and June on ornamental shrubs in the Czech Republic. There were only 29% males among the individuals; 11% of individuals were melanic. About 17% of the individuals were recorded in copula, which means that 30% of males were mating at any time. The composition of pairs indicated that melanic individuals, especially those of morph conspicua, mated more frequently than light coloured individuals and more frequently with another melanic individual. Both the choice of partner and increased activity due to the higher body temperature of sun-basking melanics might have determined these trends
Keywords: Sexual selection, female choice, colour polymorphism, Coccinellidae, equicolor